Multiple Intracerebral Hemorrhage as a Possible Presentation of Churg-Strauss Syndrome: A Rare Case Report - Prameswari, Dyandra; Ng, Peter (Acta Neurologica Indonesia, 2026)
Introduction Churg-Strauss syndrome (CSS) is a rare small-to-medium vessel vasculitis, associated with asthma, eosinophilia, and systemic inflammation. While peripheral nerve involvement is common in CSS, central nervous system (CNS) involvement is rare, with cerebral infarction and encephalopathy being the most frequent. Here, we report a rare case of multiple intracerebral hemorrhage (ICH) thought to be associated to CSS.   Case Report A 26-year-old woman with history of asthma and allergic rhinitis presented with an acute headache, worsening a day before admission, accompanied by nausea, vomiting, low-grade fever, and arthralgias. Further investigations revealed multiple cerebral hemorrhage with perifocal edema and partial sulcal enhancements bilaterally. Cerebrospinal fluid (CSF) analysis showed eosinophilic pleocytosis, with elevated Immunoglobulin E (IgE) in the blood test, suggesting cerebral vasculitis by CSS manifested in ICH. Treatment with corticosteroids and immunosuppressant was initiated, leading to a favorable outcome.   Discussion CSS is a rare systemic disorder characterized by multi-organ vasculitic involvement, though rare, CNS involvement was reported in 6–10% and ICH in association of CSS is extremely rare. The exact mechanism of CSS related cerebral bleeding remains unclear, but may result from cerebral vasculitis (indicated by raised inflammatory markers or eosinophilia), as seen in our patient.   Conclusion This case highlights that, although rare, ICH can be a manifestation of CSS-related vasculitis. Therefore, it should be considered as a differential diagnosis of ICH. In this patient, an immunosuppressive treatment using methylprednisolone and azathioprine led to a favorable outcome, emphasizing the importance of prompt intervention to minimize morbidity and mortality.